The Influence of Self-Efficacy and Employee Engagement on the Organizational Citizenship Behavior (OCB) of Civil Servants at the Office of Women's Empowerment and Child Protection in West Kalimantan - Rizma, Alda; Arninda, Arninda (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to understand the relationship between self-efficacy (X1) and employee engagement (X2) on organizational citizenship behavior (OCB) (Y). The sample in this study consists of 40 respondents who are employees at the Office of Women's Empowerment and Child Protection in West Kalimantan. The analysis methods used in this study include multiple regression analysis, correlation coefficient, determination coefficient, simultaneous test (F test), and partial test (t test). Based on multiple regression analysis, the regression equation is Y = 1.743 + 0.777X1 + 0.731X2. The multiple correlation shows an R value of 0.616, indicating a strong relationship between self-efficacy and employee engagement with OCB in this study. The determination coefficient shows an R² value of 0.380, or 38.0%. This means that the self-efficacy (X1) and employee engagement (X2) variables affect the OCB (Y) variable by 38.0%, while the remaining 62.0% is influenced or determined by other variables. The simultaneous test results show a significant value (sig) of 0.000 < 0.05, indicating that self-efficacy perception and employee engagement simultaneously have a significant effect on organizational citizenship behavior. The partial test results for the self-efficacy (X1), with a t-value of 3.243 > t-table 1.68, indicate a significant effect of the self-efficacy (X1) on organizational citizenship behavior (Y). Meanwhile, the employee engagement (X2), with a t-value of 2.026 > t-table 1.68, indicates that the employee engagement (X2) has a significant partial effect on the organizational citizenship behavior (Y).